Meta-analysis of the STEM Based Think Pair Share (TPS) Model on Students 21st Century Thinking Abilities in Indonesia - Ahmad Zain Sarnoto; Sri Tuti Rahmawati; Sisi Yulianti; Eri Mardiani; Wiwid Suryono (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
The purpose of this study was to determine the effect of STEM-based Think Pair Share (TPS) model on students' 21st century thinking skills in Indonesia. This type of research is meta-analysis research. The sources in the meta-analysis came from 15 national and international journals published in 2021-2024. The inclusion criteria in the research are that the research must be indexed by SINTA, Scopus and Web of Science, the research must be experimental or quasi-experimental related to the STEM-based Think Pair Share (TPS) model on students' 21st century thinking skills; Research data obtained through google scholar, Mendeley, Sciencedirect and ERIC, Research must be open access, and research must have complete data to calculate the effect size value. The sampling technique is purposive samling. Data analysis in this study is quantitative statistical analysis by calculating the effect size value with the help of the OpenMEE application. The results concluded that the STEM-based Think Pair Share (TPS) model had a significant effect on students' 21st century thinking skills in Indonesia with a high influence category with an average effect size value (ES = 0.952). This finding provides important information for teachers in implementing this model to encourage students' 21st century thinking skills in Indonesia.